Subterrâneos e superfícies da arte urbana: uma imersão no universo de sentidos do graffiti e da pixação da cidade de São Paulo [2002 a 2011] - Deborah Lopes Pennachin (2011)
Graffiti, one of the most intriguing manifestations of contemporary urban culture, present in almost every city around the world, has developed in Sao Paulo in a very peculiar way, amongst with pixação, its most extreme and subversive side, becoming a symbol of the biggest metropolis in Brazil. Based on transgression and on the defi ance of the rules established by society, graffi ti takes part nowadays on the offi cial art world, provoking all kinds of questioning. In this thesis we seek to understand how the processes of meaning production evoked by certain urban inscriptions in which the marginal aspect has, in one way or the other, been preserved, occur. These graffi ti are executed on the most deteriorated and forgotten places of the city, in its underground sewing galleries, on the extinct Carandiru Carcerary Complex and all around the city by the hands of pixadores, who invade the urban landscape from the ghettos that surround Sao Paulo.